STUDENT’S PERCEPTION TOWARDS SERVICES QUALITY OF ZAKAT DISTRIBUTION IN EDUCATION ISTITUTION - Nor Linda Binti Mokhtar (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The distribution of zakat in Malaysia should be able to reduce poverty in society and helpzakat recipients in fulfilling their needs. The study is to know about student’s perceptiontowards services quality of zakat distribution. The purpose of this research is todetermine the level of student’s perception towards services quality of zakat distributionand to determine the relationship between tangibles, reliability, responsiveness,assurance and empathy towards student’s perception on zakat distribution. A student’ssurvey questionnaire was utilized as the primary research instrument for this study. Thequestionnaire for this study consisted of 35 items in three parts that were Part A, Part Band Part C by using the 5 Likert scale. This study involved students in all department atPolytechnic Ungku Omar (PUO) which are from 3rd to 5th semester who receiving zakatin session December 2021 until June 2023. Descriptive analysis for 255 respondentswas obtained from questionnaire based on mean of the main research variables. Theoverall mean of student’s perception is 4.2840, tangibles is 4.0980, reliability is 4.3080,responsiveness is 4.2100, assurance is 4.2820 and empathy is 4.3040. The study showsthat medium relationships among responsiveness, reliability, assurance and students’perception towards services quality of zakat distribution. Therefore, the institution shouldimprove all service quality to gain stronger relationship such as by sending staff to attendcourses to be more open in solving problems, training staff to have more skills and beprepared to face the zakat contestants, provide classes and instructors for new staff tobe more vulnerable knowledge related to zakat. Thus, students will feel trust and relyingsolely on the institution. Lastly, the researchers need to expand the number ofrespondents in order to know more results about zakat perception among students andincluding more institutions